3D multilayered plasmonic nanostructures with high areal density for SERS. Issue 29 (23rd March 2017) - Lee, MinKyoung; Jeon, Tae Yoon; Mun, ChaeWon; Kwon, Jung-Dae; Yun, Jungheum; Kim, Shin-Hyun; Kim, Dong-Ho; Chang, Seung-Cheol; Park, Sung-Gyu
Abstract : Highly efficient 3D plasmonic nanostructures with high areal density for SERS are reported. Abstract : Enhancing light–matter interactions is essential to improving nanophotonic and optoelectronic device performance. In the present work, we developed a new design for 3D plasmonic nanostructures with enhanced near-field interactions among the plasmonic nanomaterials. The 3D plasmonic nanostructures consisted of multilayered bottom Ag/polydimethylsiloxane (PDMS) nanostructures, an alumina middle layer, and top Ag nanoparticles (NPs). High areal density PDMS nanoprotrusions were self-organized by a simple maskless plasma etching process. The conformal deposition of alumina using atomic layer deposition and Ag deposition produced 3D plasmonic nanostructures. These structures induced multiple near-field interactions between the ultrahigh-areal-density (1400 μm −2 ) top Ag NPs and the underlying Ag nanostructures, and among the top Ag NPs themselves. The high density of hot spots across the 3D space yielded highly efficient and widely tunable plasmonic responses across the entire visible range. The SERS signal enhancement measured at the 3D plasmonic nanostructures was 3.9 times the signal measured at the 2D multilayered structures and 48.0 times the signal measured at a Ag NP layer deposited onto a Si substrate. Finally, the 3D plasmonic nanostructures exhibited excellent uniformity with a variation of 6.8%, based on a microscale Raman mapping analysis. The excellent Raman signal uniformity can be attributed to the ultrahigh areal density of the Ag NPs and the uniform thickness of the alumina spacing layer.